The poetry of John Donne: Fantasy at war with reason - Jabeen, Farrah (BRAC University, 2010)
In his poetry, John Donne creates a unique style that embraces a constant battle of emerging reality and the realm of fantasy. This paper intends to show the presence of playful images and arguments, which grow even more fantastic, the more the poet is overwhelmed by the denials offered by the woman or the realities of the world. For Donne, fantasy resides beyond its ‘crude’ implication, it is a mixture of argument and inventiveness to overcome the limits of reality and here lies the ‘twist’ that Donne is so famous in making. In addition, this paper will focus on how most of Donne’s love poetry consists not of general aspiration and terms of praise but implies the existence of a very specific situation; not only daybreak or the moments before the lovers make love but where the lovers themselves are given characters almost as they would be in a drama. Moreover, how this never-ending confrontation offers no solution, does not acclaim any winner, and while doing so justify the uses of sheer wit and intelligence in Donne’s poems that portray a ‘real vs. fantastic’ domain.